OPTIMALISASI SUMBER DAYA SEKOLAH: STRATEGI PENCAPAIAN EFEKTIVITAS IMPLEMENTASI PROGRAM LITERASI GAJAHKERIS - Jati, Ratih Pramudya; Soedjono, Soedjono; Violinda, Qristin (Jurnal Manajemen Pendidikan, 2025)
The program operates within the framework of “Merdeka Belajar,” a philosophy of education in Indonesia that promotes self-directed learning. The Gajahkeris program is recognized in the education landscape as a specific school-based effort to develop literacy skills. Strong literacy will support students in understanding various subjects, thinking critically and communicating effectively. This study aims to examine how the principal uses a special approach by optimizing school resources to support the successful implementation of the Gajahkeris literacy program at SD N 03 Gajahmungkur Semarang City. This research attempts to analyze the four main dimensions that influence the successful implementation of a program or policy. This research is a qualitative research with a case study design. Data were collected through interviews, observations, and document analysis. Data analysis techniques were conducted using interactive analysis that included data reduction, data presentation, and verification/conclusion drawing. The results showed that the success of the Gajahkeris literacy program depends on the school's capacity in allocating school resources, which include personnel and infrastructure, as well as the shared commitment of all stakeholders.